PENGARUH KUNJUNGAN WISATAWAN PADA MALAM JUMAT LEGI TERHADAP PENINGKATAN OMZET PEDAGANG OLEH-OLEH (STUDI KASUS WISATA RELIGI MAKAM SUNAN GIRI GRESIK) - Faizin, Muhammad (GEMA EKONOMI, 2019)
This study aims to examine and prove the effect of tourist visits on the night of legi friday on increasing the turnover of merchants souvenirs in the religious tourism of the Sunan Giri Gresik. This research is especially important to find out about the positive changes that occur in the turnover of merchants souvenirs in the religious tourism of the Sunan Giri Gresik. This study uses a quantitative approach with simple linear analysis. The number of samples taken was 65 respondents and data collection was done by questionnaire to obtain data. The results of this study are the accountability of tourist visits on the night of Legi Friday has a significant positive effect on the increase in turnover of traders souvenirs.DOI 10.5281/zenodo.3629195